Production of Silicon Metal From Iraqi Sand - Baghdad Science Journal (مجلة بغداد للعلوم)
In this work, production of silicon metal at high purity of 99% by using Iraqi–starting materials (Iraqi sand and plant coal)was reported, electric arc–furnaces assembly was manufactured inside, the graphite electrodes were made from graphite scrap, this system is operate to produce about 800 gm /6hr of silicon metal to meet the need for manufacturing silicon oils, resins, solar cells, and electronic parts. The procedure, equipments and analysis data were described as well.